Spatial Delight and Environmental Performance of Modernist Architecture in London – Golden Lane Estate (Future Cities and Environment, 2018)
This paper investigated the spatial delight and environmental performance of the open spaces and two selected apartments in the modernist buildings at Golden Lane Estate built after the 2nd World War, between 1952 and 1961. This estate is a Grade II listed, high density, low cost housing complex designed by three young architects: Peter Chamberlin, Geoffrey Powell and Christof Bon. It was built over a bombed site and well embraced the post-war modern architecture ethos, environmental considerations and inclusion of social facilities and landscaped communal spaces. Selected communal open spaces and two apartments in different building blocks with similar attributes were chosen for this study. However, one apartment has been refurbished with internal insulation and secondary glazing for improving the comfort conditions. Through fieldwork, which included subjective observation of the spatial quality of both outdoor and indoor spaces, on-site monitoring and interview of the building occupants, first-hand information on the environmental and comfort conditions inside the apartments were obtained. Through performance based theoretical analysis, archival research and observations, the spatial quality and comfort conditions in the apartments and their energy demand were critically assessed. The research findings indicate that the design of the communal outdoor spaces in the Golden Lane Estate were well thought through and the spacing between the building blocks responded well to the requirements of spatial delight, solar and daylight access and outdoor environmental comfort. Through selective enhancement of the thermal property of the building envelope, the original naturally ventilated and well day-lit living environments were maintained while energy demand was reduced by 30%, and the overall comfort level was significantly improved. This paper presents the feasible strategies to tackle the environmental challenges in the post-war Grade II listed residential buildings in the UK.